A lithium-sulfur solid-state battery

CN122992005APending Publication Date: 2026-10-27CHINA ENERGY LITHIUM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510521167.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明旨在解决以下技术问题:现有技术中存在硫正极体积膨胀、多硫化物穿梭、锂金属负极枝晶生长、与固态电解质发生副反应、电池循环性能与安全性能差等问题

Benefits of technology

[0046]1.采用三维石墨烯负载硫构成的功能化硫正极,三维石墨烯材料具有多孔结构和高比表面积,可为硫提供均匀的负载空间,提高了硫正极活性物质的利用率,延长了电池循环寿命;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992005A_ABST
    Figure CN122992005A_ABST
Patent Text Reader

Abstract

The application discloses a lithium-sulfur solid-state battery. The lithium-sulfur solid-state battery comprises a functionalized sulfur positive electrode, a solid-state electrolyte and a lithium composite negative electrode, the active material of the functionalized sulfur positive electrode is three-dimensional graphene loaded sulfur, the three-dimensional graphene material has a porous structure and a high specific surface area, can provide uniform loading space for the sulfur, and the lithium composite negative electrode comprises a lithium / lithium alloy negative electrode and a negative electrode surface space layer, the negative electrode surface space layer is a metal organic framework material (MOFs) film. The space layer increases the mechanical strength of the lithium negative electrode interface, provides storage space for lithium ions, and reduces the generation and growth of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of batteries, and more specifically to a lithium-sulfur solid-state battery. Background Technology

[0002] Lithium-sulfur batteries have attracted much attention due to their high theoretical specific energy density (2600 Wh / kg), but their practical application still faces many challenges. Traditional liquid lithium-sulfur batteries suffer from low utilization of sulfur cathode active materials, rapid capacity decay, short cycle life, high self-discharge, and poor safety performance. The introduction of solid-state electrolytes can effectively suppress the shuttle effect of polysulfides, but the interface between the lithium metal anode and the solid-state electrolyte is unstable and prone to lithium dendrite formation, leading to internal short circuits and reduced safety performance. Simultaneously, the lithium metal anode experiences volume expansion and dendrite growth during cycling, resulting in battery failure and short cycle life. Therefore, developing lithium-sulfur solid-state batteries with high energy density, long cycle life, and excellent safety performance is crucial for the commercial application of this battery system.

[0003] Patent CN114141980A discloses a solid-state lithium-sulfur battery cathode and an all-solid-state lithium-sulfur battery. This patent reduces electrode breakage and failure caused by volume expansion by adding elemental metals to the solid-state lithium-sulfur battery cathode, solving the problems of low electronic conductivity and large volume expansion in traditional lithium-sulfur cathode systems. However, this patent still suffers from the problem of lithium dendrite growth. Summary of the Invention

[0004] This invention aims to solve the following technical problems: Existing technologies suffer from issues such as sulfur cathode volume expansion, polysulfide shuttle, lithium metal anode dendrite growth, side reactions with solid electrolytes, and poor battery cycle performance and safety. Sulfur cathode volume expansion and polysulfide shuttle can cause electrode cracking and loss of active material; lithium anode dendrite growth and severe side reactions can lead to internal short circuits and thermal runaway risks; and poor cycle performance and safety restrict the widespread application of lithium batteries. Therefore, to solve the above problems, this invention provides a lithium-sulfur solid-state battery, comprising a functionalized sulfur cathode, a solid electrolyte, and a lithium composite anode, which can effectively suppress polysulfide shuttle, reduce the generation and growth of lithium dendrites, reduce side reactions, and suppress the volume expansion of both cathode and anode.

[0005] The inventors discovered that using three-dimensional graphene as a sulfur carrier, its porous structure and high specific surface area not only effectively improve the uniformity of sulfur loading and suppress the shuttle effect of polysulfides, thus increasing the utilization rate of sulfur cathode active materials, but also mitigate volume changes during charge and discharge. The high conductivity and good mechanical strength of three-dimensional graphene also contribute to improving the rate performance and structural stability of the battery. Simultaneously, introducing a metal-organic framework (MOF) film as a spatial layer on the surface of the lithium composite anode not only significantly enhances the mechanical strength of the interface but also provides ordered storage space for lithium ions, thereby effectively suppressing the formation and growth of lithium dendrites and greatly improving the cycle stability and safety of the battery.

[0006] Specifically, the present invention provides a lithium-sulfur solid-state battery, the lithium-sulfur solid-state battery comprising:

[0007] A functionalized positive electrode, wherein the active material of the functionalized positive electrode is three-dimensional graphene-supported active sulfur;

[0008] A lithium composite anode, comprising a lithium / lithium alloy anode and a spaced-space layer on the anode surface, wherein the spaced-space layer is a metal-organic framework (MOF) film, and

[0009] A solid electrolyte positioned between a functionalized positive electrode and a lithium composite negative electrode.

[0010] In this invention, the three-dimensional graphene sulfur-locking structure of the positive electrode and the MOFs spatial layer design of the negative electrode have a synergistic enhancement effect, jointly constructing a bidirectional stabilization mechanism for lithium-sulfur solid-state batteries. On the positive electrode side, the hierarchical pores (macropores-mesopores-micropores) of the three-dimensional graphene physically confine the loaded sulfur, suppressing the loss of active materials; on the negative electrode side, the nanopores of the MOFs film not only provide a uniform lithium-ion transport path, but their mechanical strength also buffers the volume changes during lithium deposition / stripping. This positive and negative electrode linkage design forms a closed loop of "sulfur locking-lithium regulation": the sulfur-locking effect of the positive electrode reduces the corrosion of the negative electrode by polysulfides, while the stable interface of the MOFs layer on the negative electrode further reduces the short-circuit risk caused by lithium dendrites, thereby improving the overall cycle life and safety of the battery. The synergistic effect of the three-dimensional graphene and the MOFs spatial layer is essentially achieved through the structural-functional complementarity of materials, realizing the simultaneous solution of the interface problem between the sulfur positive electrode and the lithium negative electrode.

[0011] Optionally, the three-dimensional graphene-loaded active sulfur is obtained by melting and diffusing active sulfur in the pores of the three-dimensional graphene.

[0012] Optionally, the three-dimensional graphene is a three-dimensional honeycomb graphene; the pore size of the three-dimensional graphene is 500-2000 nm, and the specific surface area is 500-5000 m². 2 / g.

[0013] Optionally, the active sulfur includes elemental sulfur, sulfurized polyacrylonitrile, or a combination thereof.

[0014] Optionally, the sulfur loading of the three-dimensional graphene is 60-90%.

[0015] Optionally, the MOFs film is formed by coating a transfer film with a MOFs mixture slurry.

[0016] Optionally, the MOFs slurry comprises MOFs powder, lithium salt, binder, and hydrophilic additive.

[0017] Optionally, the MOF powder is in granular form, with a particle size D50 of 100-500 nm, a pore size of 0.1-10 Å, and a density of 0.3-0.5 g / cm³. 2 The porosity is 70%-90%; the mass ratio of MOF powder, lithium salt, binder and hydrophilic additive is (1-20):(1-5):(1-5):(0.5-2).

[0018] Optionally, the adhesion between the transfer film and the lithium composite anode is 1-8 g / inch, and the thickness is 20-100 μm.

[0019] Optionally, the thickness of the space layer is 1-100 μm and the Young's modulus is ≥6 GPa.

[0020] Optionally, the MOFs material includes MOFs materials with zinc-based, copper-based, magnesium-based, aluminum-based, cobalt-based, vanadium-based, iron-based, chromium-based, zirconium-based or lanthanide metal-based metals as metal ion or metal cluster nodes;

[0021] Preferably, the MOFs material is selected from one or a combination of at least two of the ZIF series, HKUST series, and UiO series. ZIF material is a zeolite imidazolium ester framework structure material, a porous crystalline material that regulates lithium-ion transport behavior through confinement. The ZIF series is selected from at least one of ZIF-7, ZIF-8, ZIF-63, ZIF-67, ZIF-71, and ZIF-90. HKUST material is composed of copper ions and trimesic acid ligands, possessing a three-dimensional cubic pore network that generates two different sizes of mesoporous cages. The HKUST series is selected from at least one of HKUST-1 and HKUST-2. UiO material is composed of zirconium ions and organic ligands, exhibiting a highly tunable crystal structure. Pore size can be precisely controlled through ligand substitution. The UiO series is selected from at least one of UiO-66, UiO-67, UiO-68, UiO-76, UiO-77, and UiO-84.

[0022] Optionally, the lithium salt includes one or more combinations of lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bisfluorosulfonylimide, lithium bistrifluoromethanesulfonylimide, lithium dioxalateborate, lithium difluorooxalateborate, lithium carbonate, lithium oxalate, lithium bicarbonate, lithium acetate, lithium halides, lithium sulfate, and lithium hydroxide.

[0023] Optionally, the adhesive comprises one or a combination of at least two of the following: polyvinyl alcohol, polyethylene oxide, polybutene-styrene, polystyrene-butadiene copolymer, polyvinylidene fluoride, polystyrene, polycarboxylic cellulose, cyanoacrylate, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organofluoropolymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethylparaben, and their derivatives.

[0024] Optionally, the hydrophilic additive includes one or more combinations of carboxylates, sulfonates, sulfates, phosphates, imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.

[0025] Optionally, the transfer film material includes an organic material selected from one or more of polyvinylidene fluoride, polyvinyl chloride, polyethylene, polypropylene, polystyrene, styrene-butadiene-vinyl nitrile copolymer, polyimide, polycarbonate, phenolic plastics, polyoxymethylene, polyethylene terephthalate, styrene-modified polymethacrylic acid, polysulfone, polytetrafluoroethylene, amino plastics, and epoxy resin, or their homopolymers or copolymers.

[0026] Optionally, the lithium / lithium alloy anode includes one or a combination of metallic lithium anode, lithium alloy anode, and lithium alloy anode.

[0027] Preferably, the lithium alloy anode comprises an alloy of lithium with one or more of silicon, indium, silver, carbon, magnesium, aluminum, boron, tin, gallium, cobalt, gold, barium, bismuth, calcium, germanium, mercury, platinum, zinc, lead, antimony, cadmium, and cobalt.

[0028] The thickness of the lithium / lithium alloy anode is 3μm-300μm, preferably 10μm-100μm.

[0029] Optionally, the thickness ratio of the space layer to the lithium / lithium alloy anode is (0.001-1):1, preferably (0.01-0.1):1.

[0030] Optionally, the solid electrolyte comprises one or more of the following: sulfide solid electrolyte, oxide solid electrolyte, halide solid electrolyte, polymer solid electrolyte, or organic-inorganic composite solid electrolyte.

[0031] Optionally, both the functionalized positive electrode and the lithium composite negative electrode include a current collector, which includes at least one of copper foil, aluminum foil, stainless steel foil, nickel foil, tin foil, carbon nanotube paper, carbon fiber paper, copper mesh, aluminum mesh, stainless steel mesh, nickel foam, and organic fiber film with metal plating on the surface.

[0032] Another aspect of the present invention provides a method for preparing a lithium-sulfur solid-state battery as described above, the method comprising:

[0033] (1) Preparation of three-dimensional graphene-supported sulfur mixture: sulfur powder is mixed with three-dimensional graphene and heated to the melting point of sulfur (115°C) to melt the sulfur and penetrate into the pores of graphene to obtain a three-dimensional graphene-supported sulfur mixture.

[0034] (2) Preparation of functionalized positive electrode: The above three-dimensional graphene-supported sulfur mixture is uniformly mixed with a binder, and a solvent is optionally added; the prepared mixed slurry is loaded onto the surface of the current collector and dried to obtain a functionalized positive electrode film;

[0035] (3) Preparation of lithium composite anode space layer: MOFs material, lithium salt, binder and hydrophilic additive are uniformly mixed, and an optional solvent is added and stirred to obtain a mixed slurry. The mixed slurry is placed on the transfer film and dried to obtain lithium composite anode space layer.

[0036] (4) Preparation of lithium composite anode: The space layer film is rolled onto the surface of the lithium / lithium alloy anode and the tabs are welded to obtain the lithium composite anode;

[0037] (5) Assemble lithium-sulfur solid-state batteries: Assemble functionalized positive electrode, solid electrolyte, lithium composite negative electrode and encapsulation materials into lithium-sulfur solid-state batteries.

[0038] Optionally, the uniform mixing method in step (1) is ball milling, wherein the ball milling speed is 100-600 rpm and the ball milling time is 3-6 h.

[0039] Optionally, the adhesive in step (2) includes at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), sodium alginate (SA), polyethylene oxide (PEO), or polyimide (PI).

[0040] Optionally, the drying in steps (2) and (3) is carried out at 80-100°C for 8-12 hours.

[0041] Optionally, the solvents described in steps (2) and (3) include any one or a combination of at least two of N-methylpyrrolidone, tetrahydrofuran, dimethyl ethyl ether, dichloromethane, ethylene carbonate, dimethyl carbonate, diethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene glycol dimethyl ether, diethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, dimethyl sulfate, and polyetherketone.

[0042] Optionally, in step (2), the three-dimensional graphene loaded with sulfur: binder: solvent = (5-10): (2-3): (87-93)

[0043] Optionally, the method of applying the slurry to the transfer film in step (3) includes any one or a combination of at least two of coating, spraying, spin coating, rolling, and impregnation.

[0044] Optionally, in step (4), the pressure at which the space layer obtained in step (3) is rolled onto the lithium / lithium alloy anode is 10-20 kN.

[0045] This invention has at least one of the following beneficial technical effects:

[0046] 1. A functionalized sulfur cathode composed of sulfur supported by three-dimensional graphene. The three-dimensional graphene material has a porous structure and high specific surface area, which can provide a uniform loading space for sulfur, improve the utilization rate of sulfur cathode active material, and extend battery cycle life.

[0047] 2. A lithium composite anode is constructed using a lithium / lithium alloy anode and a metal-organic framework (MOF) space layer on the anode surface. The MOF space layer increases the mechanical strength of the lithium anode interface, provides storage space for lithium ions, effectively reduces the generation and growth of lithium dendrites, and improves the safety performance of the battery.

[0048] 3. The introduction of solid electrolytes suppresses the shuttle effect of polysulfides, further improving the cycle stability of the battery;

[0049] 4. In lithium composite anodes, lithium / lithium alloy anodes have certain mechanical strength, eliminating the need to increase the thickness of the lithium strip and saving on the amount of lithium anode used;

[0050] 5. The lithium-sulfur solid-state battery of the present invention combines high energy density, long cycle life and excellent safety performance, which is conducive to the commercial application of this battery system. Attached Figure Description

[0051] Figure 1 This is a schematic diagram of the lithium-sulfur solid-state battery structure of the present invention;

[0052] Figure 2 This is a schematic diagram of lithium-ion deposition when the lithium composite anode of the present invention is applied to a lithium-sulfur solid-state battery;

[0053] Figure 3 This is a 1000x magnified SEM image of the three-dimensional graphene-loaded sulfur cathode of the lithium-sulfur solid-state battery in Example 1.

[0054] Figure 4 The image shows a 3000x magnified SEM image of the lithium composite anode space layer after 300 cycles of the lithium-sulfur solid-state battery in Example 1.

[0055] Figure 5 The cycling test curves of the lithium-sulfur solid-state batteries in Examples 1, 2, 3 and Comparative Example 1 at a charge-discharge current of 0.5C are shown.

[0056] Among them, 1-positive current collector, 2-functionalized sulfur positive electrode, 3-solid electrolyte, 4-space layer, 5-lithium / lithium alloy negative electrode, 6-negative current collector. Detailed Implementation

[0057] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0058] An example illustrating the structure of the lithium-sulfur solid-state battery provided by this invention is shown in the schematic diagram below. Figure 1 As shown. The functionalized positive electrode includes a positive electrode current collector 1 and a functionalized sulfur positive electrode 2; the lithium composite negative electrode includes a space layer 4, a lithium / lithium alloy negative electrode 5, and a negative electrode current collector 6. A solid electrolyte 3 is located between the functionalized positive electrode and the lithium composite negative electrode, wherein the solid electrolyte 3 is in contact with the space layer 4.

[0059] Example 1

[0060] This embodiment provides a lithium-sulfur battery, comprising a functionalized positive electrode consisting of 1000 nm pore size three-dimensional graphene loaded with 80% elemental sulfur, a sulfide solid electrolyte, a 10 μm thick MOF (Metal-O-Factory) space layer, and a 50 μm thick lithium metal negative electrode. The MOF space layer is composed of ZIF-8 with a 3 Å pore size, lithium hexafluorophosphate (LiPF6), polyethylene oxide (PEO), N-ethylpyridine bromide, and N-methylpyrrolidone (NMP) as solvent, with a ZIF-8:LiPF6:PEO:N-ethylpyridine bromide:NMP ratio of 10:3:2:1:84, and a Young's modulus of 6 GPa. The positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0061] The method for preparing the lithium-sulfur battery includes the following steps:

[0062] (1) Preparation of three-dimensional graphene-supported sulfur mixture: Sulfur powder and three-dimensional graphene are ball-milled at 600 rpm for 3 h, and heated to the melting point of sulfur 115℃ to melt the sulfur and penetrate into the pores of graphene to obtain three-dimensional graphene-supported sulfur mixture.

[0063] (2) Preparation of functionalized positive electrode: The above three-dimensional graphene-supported sulfur mixture is uniformly mixed with polystyrene butadiene copolymer (SBR) and NMP; the prepared mixed slurry is loaded onto the surface of the current collector and dried at 80°C to obtain a functionalized positive electrode film;

[0064] (3) Preparation of lithium composite anode space layer: ZIF-8, LiPF6, PEO, N-ethylpyridine bromide and NMP are uniformly mixed to obtain a mixed slurry. The mixed slurry is coated on a 30 μm PET film and dried at 80℃ to obtain a lithium composite anode space layer.

[0065] (4) Preparation of lithium composite anode: Press the space layer film material with a 10kN force roller onto the surface of the lithium / lithium alloy anode, and weld the electrode tabs to obtain the lithium composite anode;

[0066] (5) Assemble lithium-sulfur solid-state batteries: Assemble functionalized positive electrode, solid electrolyte, lithium composite negative electrode and encapsulation materials into lithium-sulfur solid-state batteries.

[0067] Example 2

[0068] This embodiment provides a lithium-sulfur battery, comprising a functionalized positive electrode consisting of 1500 nm pore size three-dimensional graphene loaded with 80% elemental sulfur, a sulfide solid electrolyte, a 10 μm thick MOF (Metal-O-Fractions) space layer, and a 50 μm thick lithium metal negative electrode. The MOF space layer is composed of HKUST-1 with a 5 Å pore size, lithium bis(fluorosulfonyl)imide (LiFSI), SBR, sodium dodecylbenzenesulfonate (SDBS), and dimethyl ethylene glycol (DME) solvent, with a ratio of HKUST-1:LiFSI:SBR:SDBS:DME = 10:3:2:1:84 and a Young's modulus of 8 GPa. The positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0069] The method for preparing the lithium-sulfur battery includes the following steps:

[0070] (1) Preparation of three-dimensional graphene-supported sulfur mixture: Sulfur powder and three-dimensional graphene are ball-milled at 600 rpm for 3 h, and heated to the melting point of sulfur 115℃ to melt the sulfur and penetrate into the pores of graphene to obtain three-dimensional graphene-supported sulfur mixture.

[0071] (2) Preparation of functionalized positive electrode: The above three-dimensional graphene-supported sulfur mixture is uniformly mixed with SBR and NMP; the prepared mixed slurry is loaded onto the surface of the current collector and dried at 80°C to obtain a functionalized positive electrode film;

[0072] (3) Preparation of lithium composite anode space layer: HKUST-1, LiFSI, SBR, SDBS and DME are uniformly mixed to obtain a mixed slurry. The mixed slurry is coated on a 30 μm PET film and dried at 80℃ to obtain a lithium composite anode space layer.

[0073] (4) Preparation of lithium composite anode: Press the space layer film material with a 10kN force roller onto the surface of the lithium / lithium alloy anode, and weld the electrode tabs to obtain the lithium composite anode;

[0074] (5) Assemble lithium-sulfur solid-state batteries: Assemble functionalized positive electrode, solid electrolyte, lithium composite negative electrode and encapsulation materials into lithium-sulfur solid-state batteries.

[0075] Example 3

[0076] This embodiment provides a lithium-sulfur battery, comprising a functionalized positive electrode consisting of 1000 nm pore size three-dimensional graphene supported on 80% sulfurized polyacrylonitrile, a sulfide solid electrolyte, a 10 μm thick MOF (Metal-O-Fractions) space layer, and a 50 μm thick lithium metal negative electrode. The MOF space layer is composed of 6 Å pore size UiO-66, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyvinylidene fluoride (PVDF), 1-methylimidazolium chloride, and dimethyl carbonate as solvent, with a ratio of UiO-66:LiTFSI:PVDF:1-methylimidazolium chloride:dimethyl carbonate = 10:3:1:1:85, and a Young's modulus of 10 GPa. The positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0077] The method for preparing the lithium-sulfur battery includes the following steps:

[0078] (1) Preparation of three-dimensional graphene-supported sulfur mixture: Sulfur powder and three-dimensional graphene are ball-milled at 600 rpm for 3 h, and heated to the melting point of sulfur 115℃ to melt the sulfur and penetrate into the pores of graphene to obtain three-dimensional graphene-supported sulfur mixture.

[0079] (2) Preparation of functionalized positive electrode: The above three-dimensional graphene-supported sulfur mixture is uniformly mixed with SBR and NMP; the prepared mixed slurry is loaded onto the surface of the current collector and dried to obtain a functionalized positive electrode film;

[0080] (3) Preparation of lithium composite anode space layer: UiO-66, LiTFSI, PVDF, 1-methylimidazolium chloride and dimethyl carbonate are uniformly mixed to obtain a mixed slurry. The mixed slurry is coated on a 30 μm PET film and dried to obtain a lithium composite anode space layer.

[0081] (4) Preparation of lithium composite anode: Press the space layer film material with a 10kN force roller onto the surface of the lithium / lithium alloy anode, and weld the electrode tabs to obtain the lithium composite anode;

[0082] (5) Assemble lithium-sulfur solid-state batteries: Assemble functionalized positive electrode, solid electrolyte, lithium composite negative electrode and encapsulation materials into lithium-sulfur solid-state batteries.

[0083] Example 4

[0084] Compared with Example 1, the only difference is that the amount of elemental sulfur supported on the three-dimensional graphene is replaced with 60%, while the other conditions remain the same.

[0085] Example 5

[0086] Compared with Example 1, the only difference is that the amount of elemental sulfur loaded on the three-dimensional graphene is replaced with 90%, while the other conditions remain the same.

[0087] Example 6

[0088] Compared with Example 1, the only difference is that the solid electrolyte is replaced with an oxide solid electrolyte, while the other conditions remain the same.

[0089] Example 7

[0090] Compared with Example 1, the only difference is that the MOF space layer thickness is replaced with 1 μm, while the other conditions remain the same.

[0091] Example 8

[0092] Compared with Example 1, the only difference is that the MOF space layer thickness is replaced with 100 μm, while the other conditions remain the same.

[0093] Example 9

[0094] Compared with Example 1, the only difference is that the ZIF8 content in the slurry is replaced with 20% by mass, while the other conditions remain the same.

[0095] Example 10

[0096] Compared with Example 1, the only difference is that the ZIF8 content in the slurry mass ratio is replaced with 1%, while the other conditions remain unchanged.

[0097] Example 11

[0098] Compared with Example 1, the only difference is that the proportion of LiPF6 in the slurry is replaced with 5% by mass, while the other conditions remain the same.

[0099] Example 12

[0100] Compared with Example 1, the only difference is that the proportion of LiPF6 in the slurry is replaced with 1% by mass, while the other conditions remain the same.

[0101] Example 13

[0102] Compared with Example 1, the only difference is that the proportion of PEO in the slurry is replaced with 5%, while the other conditions remain the same.

[0103] Example 14

[0104] Compared with Example 1, the only difference is that the proportion of PEO in the slurry is replaced with 1%, while the other conditions remain the same.

[0105] Example 15

[0106] Compared with Example 1, the only difference is that the hydrophilic additive is replaced with 2% of the slurry mass, while the other conditions remain the same.

[0107] Example 16

[0108] Compared with Example 1, the only difference is that the hydrophilic additive is replaced with 0.5% of the slurry mass, while the other conditions remain the same.

[0109] Example 17

[0110] Compared with Example 1, the only difference is that the lithium metal anode is replaced with a 5μm electrode, while the other conditions remain the same.

[0111] Example 18

[0112] Compared with Example 1, the only difference is that the lithium metal anode is replaced with a 100μm electrode, while the other conditions remain the same.

[0113] Example 19

[0114] Compared with Example 1, the only difference is that the lithium metal anode is replaced with a lithium aluminum alloy anode, while the other conditions remain the same.

[0115] Example 20

[0116] Compared with Example 1, the only difference is that the space layer is applied to the transfer film using a spraying method, while all other conditions remain the same.

[0117] Comparative Example 1

[0118] This comparative example provides a lithium-sulfur solid-state battery. Compared with Example 1, elemental sulfur is coated on aluminum foil as the positive electrode, no space layer is added, and a 50μm lithium metal strip is used as the negative electrode, while other conditions remain unchanged.

[0119] Comparative Example 2

[0120] This comparative example provides a lithium-sulfur solid-state battery. Compared with Comparative Example 1, the sulfide solid electrolyte is replaced with an oxide solid electrolyte, while the other conditions remain unchanged.

[0121] Comparative Example 3

[0122] This comparative example provides a lithium-sulfur solid-state battery. Compared with Example 1, elemental sulfur is coated on aluminum foil as the positive electrode, while other conditions remain unchanged.

[0123] Comparative Example 4

[0124] This comparative example provides a lithium-sulfur solid-state battery that, compared to Example 1, does not add a space layer, uses a 50μm lithium metal strip as the negative electrode, and keeps all other conditions unchanged.

[0125] Comparative Example 5

[0126] This comparative example provides a lithium-sulfur solid-state battery. Compared with Example 1, a two-dimensional graphene sheet loaded with elemental sulfur coated on an aluminum foil is used as the positive electrode, while the other conditions remain unchanged.

[0127] Comparative Example 6

[0128] This comparative example provides a lithium-sulfur solid-state battery. Compared with Example 2, elemental sulfur plus metal additives (nano silver particles with a particle size D50 of 80 nm) are coated on aluminum foil as the positive electrode, while the other conditions remain unchanged.

[0129] Comparative Example 7

[0130] This comparative example provides an all-solid-state battery that, compared to Example 1, does not contain MOF materials in its space layer, while the other conditions are the same as in Example 1.

[0131] Comparative Example 8

[0132] This comparative example provides an all-solid-state battery that, compared to Example 1, does not contain lithium salt in its space layer, while the other conditions are the same as in Example 1.

[0133] Comparative Example 9

[0134] This comparative example provides an all-solid-state battery that, compared to Example 1, does not contain a binder in its space layer, while the other conditions are the same as in Example 1.

[0135] Comparative Example 10

[0136] This comparative example provides an all-solid-state battery that, compared to Example 1, does not contain hydrophilic additives in its space layer, while the other conditions are the same as in Example 1.

[0137] Comparative Example 11

[0138] This comparative example provides an all-solid-state battery. Compared with Example 1, its spatial layer is replaced with a transfer Al2O3 coating, and the other conditions are the same as those in Example 1.

[0139] Comparative Example 12

[0140] This comparative example provides an all-solid-state battery, which, compared to Example 1, has its spacer layer replaced with a LiF coating, while the other conditions are the same as in Example 1.

[0141] The preparation method of lithium-sulfur solid-state batteries is as follows:

[0142] Take 100mg of solid electrolyte and press it into a Teflon tablet mold at a pressure of 300MPa to obtain an electrolyte layer; press the obtained functionalized positive electrode sheet onto one side of the solid electrolyte at a pressure of 300MPa, and then press the lithium composite negative electrode onto the other side of the electrolyte layer at a pressure of 20MPa to obtain an all-solid-state battery.

[0143] Lithium-sulfur solid-state battery performance testing:

[0144] Solid-state batteries were assembled using the positive and negative electrodes provided in Examples 1-20 and Comparative Examples 1-10, respectively, and their cycle performance was tested. The specific test method was as follows: constant current charging and constant current discharging were performed at 25°C, with a charging and discharging voltage range of 1.7-2.8V and a charging and discharging rate of 0.5C. The initial capacity of the battery was recorded as C0. One full charge and discharge cycle was recorded as one cycle. The charging and discharging were performed according to the above method, and the capacity of the battery was tested after each cycle until the battery capacity was 80% of C0, or the battery experienced a short circuit or the charging and discharging efficiency was less than 98%. The number of cycles at this point was recorded.

[0145] Young's modulus test of lithium composite anode:

[0146] A space layer was placed on a lithium metal anode, and Young's modulus was measured at the anode interface. Using an atomic force microscope, one end of a microcantilever, highly sensitive to minute forces, was fixed, while the other end had a tiny needle tip that gently contacted the interface. During scanning, the repulsive force between the tip and the interface was kept constant. The microcantilever with the tip moved undulating perpendicular to the interface, corresponding to the equipotential surface of the interatomic forces between the tip and the interface. Using optical detection or tunneling current detection, the positional changes of the microcantilever at various scanning points could be measured, thus obtaining the sample morphology and calculating the Young's modulus.

[0147] Adhesion test of transfer film to lithium composite anode:

[0148] Using a tensile testing machine, the transfer film and lithium composite negative electrode were peeled off at a uniform speed at an angle of 180°, and the maximum force value during the peeling process was recorded to evaluate the adhesion strength.

[0149] The cycle performance test results of the lithium-sulfur all-solid-state batteries prepared using Examples 1-20 and Comparative Examples 1-11 are shown in Table 1.

[0150] Table 1 Battery Cycle Performance Test Results

[0151]

[0152] Battery cycle performance test analysis results:

[0153] (1) Comparison of Examples 1-3 and Comparative Example 1

[0154] Examples 1-3 demonstrate the improvement in cycle performance of lithium-sulfur solid-state batteries by the proposed lithium-sulfur battery structure. The positive electrode in Examples 1-3 is prepared by coating three-dimensional graphene-supported sulfur onto aluminum foil, and the negative electrode is a lithium composite negative electrode. The composite structure uses different MOF materials as spatial layers transferred onto the surface of a lithium / lithium alloy metal strip. The structure of the lithium-sulfur solid-state battery is as follows: Figure 1 As shown in the diagram, a schematic diagram of lithium-ion deposition in a lithium composite anode is as follows: Figure 2 As shown. The three-dimensional graphene cathode achieves dual sulfur locking through physical confinement of the honeycomb structure and chemical adsorption (e.g., Figure 3 This not only increases the sulfur loading but also effectively suppresses the shuttle effect of polysulfides. The negative electrode adopts a lithium composite design combined with MOF space layers. Figure 4 The image shows a 3000x magnified SEM image of the lithium composite anode space layer after 300 cycles of a lithium-sulfur solid-state battery. The regular channel structure of MOFs can uniformly guide lithium-ion flow and suppress dendrite growth. Its mechanical strength can buffer volume changes during cycling, while the transfer process ensures tight interface contact. Combined with the data in Table 1 and... Figure 5 Compared with Comparative Example 1, the lithium-sulfur solid-state battery designed in this invention improves the battery cycle life by 90-93 cycles at a charge / discharge rate of 0.5C.

[0155] (2) Comparison of Example 1 and Examples 4-5

[0156] Examples 4-5 illustrate the effect of varying the sulfur loading in three-dimensional graphene on the cycle performance of lithium-sulfur solid-state batteries. Data from Table 1 shows that when the sulfur loading in three-dimensional graphene is 60%, the utilization rate of the sulfur active material is high, effectively mitigating volume expansion, but the overall energy density of the battery is low. When the sulfur loading in three-dimensional graphene is 90%, sulfur tends to be unevenly distributed, the utilization rate of the active material decreases, mechanical stress during charge and discharge processes intensifies, leading to structural collapse and interfacial contact failure, thus reducing cycle performance. Therefore, it is necessary to balance the sulfur loading to consider both the energy density and long-term cycle stability of lithium-sulfur solid-state batteries.

[0157] (3) Comparison of Example 6 and Comparative Example 2

[0158] Example 6 and Comparative Example 2 illustrate the effect of the lithium-sulfur solid-state battery proposed in this invention on cycle performance in different types of solid electrolytes. The data in Table 1 show that in oxide electrolytes, the lithium-sulfur solid-state battery cycled 80 times more. The combination of three-dimensional graphene sulfur locking and lithium composite anode in sulfide solid electrolytes can suppress polysulfide shuttle, improve interfacial contact in oxide electrolytes or other solid electrolytes, and the flexible interface of MOFs can adapt to electrolyte deformation and reduce interfacial impedance.

[0159] (4) Comparison of Example 1 and Examples 7-18

[0160] Examples 7-18 illustrate the thickness and composition of the space layer in the lithium composite anode, and the impact of changes in the thickness of the active material layer on the cycle performance of lithium-sulfur solid-state batteries. Data in Table 1 shows that the thickness of the MOF space layer directly affects lithium-ion transport and dendrite suppression: too thin a layer results in insufficient mechanical strength, making it difficult to effectively block dendrites; too thick a layer increases interfacial impedance and reduces rate performance. The ratio of MOFs / binder / lithium salt / hydrophilic additive needs to be optimized synergistically. High MOF content enhances ion storage and mechanical support, but excessive MOFs increase interfacial impedance; too much binder clogs pores, while too little reduces the mechanical properties of the space layer; lithium salt improves ionic conductivity, but excessive amounts can easily trigger side reactions, while insufficient amounts reduce ion conduction performance; hydrophilic additives reduce the surface tension of the solution on the transfer film, but their content needs to be controlled to avoid interfacial instability. The thickness of the lithium metal layer affects the battery's energy density and cycle performance; too thin a layer easily leads to local depletion and short circuits, while too thick a layer exacerbates volume expansion.

[0161] (5) Comparison of Example 1 and Example 19

[0162] Example 19 illustrates the effect of different lithium alloy anodes on the cycle performance of lithium-sulfur solid-state batteries. By introducing other metallic elements (such as magnesium, aluminum, and zinc), the lithium alloy layer can alter the deposition behavior of lithium, making it more uniform and effectively suppressing the formation of lithium dendrites, thus reducing the risk of short circuits. Simultaneously, alloying improves the mechanical strength of the material, enabling it to better withstand volume changes during charge and discharge, maintaining the integrity of the electrode structure. As shown in Table 1, the cycle performance of the lithium alloy composite battery is improved, with an increase of 33 cycles at a 0.5C charge / discharge rate.

[0163] (6) Comparison of Example 1 and Example 20

[0164] Example 20 illustrates the impact of different transfer processes for the space reinforcement layer on the performance of lithium-sulfur solid-state batteries. The coating method is replaced with a spraying method. The spraying method requires ensuring the uniformity of the space reinforcement layer slurry sprayed onto the transfer surface and controlling the surface tension of the lithium metal strip during drying. By controlling the process parameters, different coating processes can be substituted.

[0165] (7) Comparison of Example 1 and Comparative Examples 3-4

[0166] Comparative Examples 3-4 illustrate the impact of not employing 3D graphene for sulfur locking and not adding a space layer on the cycle performance of lithium-sulfur solid-state batteries. Compared to the optimized structure employing 3D graphene for sulfur locking in the cathode and MOFs space layer modification in the anode, the simplified design of the lithium-sulfur solid-state battery shows a significant decrease in cycle performance. Without 3D graphene for sulfur locking in the cathode, sulfur active materials are prone to agglomeration and loss, leading to intensified polysulfide shuttle in the solid electrolyte, resulting in irreversible loss of active materials and rapid capacity decay. Without introducing a MOF space layer in the anode, lithium metal will generate dendrites during cycling due to uneven ion flow distribution, exacerbating lithium metal pulverization. As shown in Table 1, the battery lacking a 3D graphene-functionalized cathode exhibits a capacity retention of less than 80% after 80 cycles, while the anode without a MOF space layer shows significant failure after 96 cycles. This highlights the crucial role of 3D graphene for sulfur locking and the MOF space layer in stabilizing the interface and suppressing side reactions.

[0167] (8) Comparison of Example 1 and Comparative Examples 5-6

[0168] Comparative Examples 5-6 illustrate the impact of different carbon materials loaded with sulfur or the addition of metal additives to form functionalized cathodes on the cycle performance of lithium-sulfur solid-state batteries. Compared to the simple physical adsorption of sulfur loaded on two-dimensional graphene sheets, the three-dimensional graphene honeycomb structure exhibits multi-dimensional advantages in sulfur locking within lithium-sulfur batteries. In terms of spatial confinement, the interpenetrating porous network of three-dimensional graphene can provide a sulfur loading rate of up to 90%, and its hierarchical channels can both encapsulate elemental sulfur and reserve mesoporous channels for the electrolyte. Regarding conductivity, the bulk conductivity of the three-dimensional continuous graphene framework is two orders of magnitude higher than that of the two-dimensional sheet stacked structure, effectively solving the insulation problem of the sulfur cathode. In terms of mechanical properties, the three-dimensional honeycomb structure can withstand 300% sulfur volume expansion without collapse, while two-dimensional graphene sheets exhibit significant structural delamination after cycling. This synergistic effect of the "micro-nano cage" confinement effect and the conductive framework results in electrochemical performance far exceeding that of the two-dimensional graphene system. Metal additives cannot provide the same physical confinement space as three-dimensional graphene, making it difficult to completely suppress the diffusion of polysulfides. Furthermore, high loading may lead to increased electrode density and reduced energy density.

[0169] (9) Comparison of Example 1 and Comparative Examples 7-10

[0170] Comparative Examples 7-10 illustrate the importance of the spatial layer composition materials proposed in this invention and their impact on the cycle performance of lithium-sulfur solid-state batteries. The absence of any component in the MOF spatial layer affects the cycle performance of lithium-sulfur solid-state batteries: The lack of MOF powder prevents effective lithium-ion storage and regulation of lithium-ion deposition, leading to uncontrolled lithium dendrite growth and a high risk of short circuits; the lack of lithium salt reduces the ionic conductivity of the interface layer, exacerbating battery polarization and causing rapid capacity decay; the lack of binder results in insufficient mechanical strength of the MOF layer, causing structural collapse during cycling and failing to buffer the volume changes of the lithium anode; and the absence of hydrophilic additives reduces interfacial wettability, significantly increasing surface tension on the transfer film. The synergistic effect of different components in the MOF spatial layer is crucial for maintaining a stable lithium deposition interface.

[0171] (10) Comparison of Example 1 and Comparative Examples 11-12

[0172] Comparative Examples 11-12 illustrate the impact of different space layer materials on the cycling performance of lithium-sulfur solid-state batteries. Compared to traditional Al₂O₃ or LiF interlayer materials, MOFs exhibit significant advantages as space layer materials in lithium-sulfur solid-state batteries. Structurally, the regular nanopores of MOFs can precisely control lithium-ion flux, achieving uniform deposition, while the disordered pores of alumina and the dense structure of lithium fluoride are less effective in controlling uniform lithium-ion deposition. The organic ligands of MOFs can anchor polysulfides through chemisorption, suppressing the shuttle effect, while alumina / lithium fluoride only provides physical barriers. Regarding interfacial compatibility, the flexible framework of MOFs can adapt to changes in the volume of lithium metal, while rigid alumina is prone to cracking, and lithium fluoride is susceptible to phase transition stripping during cycling. The multifunctional integrated characteristics of MOFs (ion conduction + dendrite suppression + polysulfide adsorption) make them an ideal choice for high-performance lithium-sulfur solid-state batteries.

[0173] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.

Claims

1. A lithium-sulfur solid-state battery, characterized in that, The lithium-sulfur solid-state battery includes: A functionalized positive electrode, wherein the active material of the functionalized positive electrode is three-dimensional graphene-supported active sulfur; A lithium composite anode, comprising a lithium / lithium alloy anode and a spaced-space layer on the anode surface, wherein the spaced-space layer is a metal-organic framework (MOF) film. A solid electrolyte positioned between a functionalized positive electrode and a lithium composite negative electrode.

2. The lithium-sulfur solid-state battery according to claim 1, characterized in that, The three-dimensional graphene-supported active sulfur is obtained by melting and diffusing active sulfur in the pores of three-dimensional graphene; The three-dimensional graphene is a three-dimensional honeycomb graphene; The three-dimensional graphene has a pore size of 500-2000 nm and a specific surface area of ​​500-5000 m². 2 / g; The active sulfur includes elemental sulfur, sulfurized polyacrylonitrile, or a combination thereof; The sulfur loading of the three-dimensional graphene is 60-90%.

3. The lithium-sulfur solid-state battery according to claim 1, characterized in that, The MOFs film is formed by coating a transfer film with a MOFs mixture slurry; The MOFs mixed slurry contains MOFs powder, lithium salt, binder, and hydrophilic additive; The MOF powder is in granular form with a particle size D50 of 100-500 nm, a pore size of 0.1-10 Å, and a density of 0.3-0.5 g / cm³. 2 The porosity is 70%-90%; The mass ratio of MOF powder, lithium salt, binder and hydrophilic additive is (1-20):(1-5):(1-5):(0.5-2). The adhesion between the transfer film and the lithium composite negative electrode is 1-8 g / inch, and the thickness is 20-100 μm; The thickness of the space layer is 1-100 μm and the Young's modulus is ≥6 GPa.

4. The lithium-sulfur solid-state battery according to any one of claims 1-3, characterized in that, The MOFs materials include MOFs materials with zinc-based, copper-based, magnesium-based, aluminum-based, cobalt-based, vanadium-based, iron-based, chromium-based, zirconium-based, or lanthanide metal-based metals as metal ion or metal cluster nodes. Preferably, the MOFs material is selected from one or a combination of at least two of the ZIF series, HKUST series, and UiO series; the ZIF series is selected from at least one of ZIF-7, ZIF-8, ZIF-63, ZIF-67, ZIF-71, and ZIF-90; the HKUST series is selected from at least one of HKUST-1 and HKUST-2; and the UiO series is selected from at least one of UiO-66, UiO-67, UiO-68, UiO-76, UiO-77, and UiO-84. The lithium salts include one or more combinations of lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium dioxalateborate, lithium difluorooxalateborate, lithium carbonate, lithium oxalate, lithium bicarbonate, lithium acetate, lithium halides, lithium sulfate, and lithium hydroxide. The adhesive comprises one or a combination of at least two of the following: polyvinyl alcohol, polyethylene oxide, polybutene-styrene, polystyrene-butadiene copolymer, polyvinylidene fluoride, polystyrene, polycarboxylic cellulose, cyanoacrylate, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organofluoropolymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethylparaben, and their derivatives; The hydrophilic additives include one or more combinations of carboxylates, sulfonates, sulfates, phosphates, imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphorus ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids. The transfer film material includes organic materials, which are selected from one or more of polyvinylidene fluoride, polyvinyl chloride, polyethylene, polypropylene, polystyrene, styrene-butadiene-vinyl nitrile copolymer, polyimide, polycarbonate, phenolic plastics, polyoxymethylene, polyethylene terephthalate, styrene-modified polymethacrylic acid, polysulfone, polytetrafluoroethylene, amino plastics, and epoxy resin, or their homopolymers or copolymers.

5. The lithium-sulfur solid-state battery according to any one of claims 1-4, characterized in that, The lithium / lithium alloy anode includes one or a combination of metallic lithium anode and lithium alloy anode. Preferably, the lithium alloy anode comprises an alloy of lithium with one or more of silicon, indium, silver, carbon, magnesium, aluminum, boron, tin, gallium, cobalt, gold, barium, bismuth, calcium, germanium, mercury, platinum, zinc, lead, antimony, cadmium, and cobalt. The thickness of the lithium / lithium alloy anode is 3μm-300μm, preferably 10μm-100μm; The thickness ratio of the space layer to the lithium / lithium alloy anode is (0.001-1):1, preferably (0.01-0.1):

1.

6. The lithium-sulfur solid-state battery according to any one of claims 1-5, characterized in that, The solid electrolyte comprises one or more of the following: sulfide solid electrolyte, oxide solid electrolyte, halide solid electrolyte, polymer solid electrolyte, or organic-inorganic composite solid electrolyte.

7. The lithium-sulfur solid-state battery according to any one of claims 1-6, characterized in that, Both the functionalized positive electrode and the lithium composite negative electrode include a current collector, which includes at least one of copper foil, aluminum foil, stainless steel foil, nickel foil, tin foil, carbon nanotube paper, carbon fiber paper, copper mesh, aluminum mesh, stainless steel mesh, nickel foam, and organic fiber film with metal plating on the surface.

8. A method for preparing a lithium-sulfur solid-state battery as described in any one of claims 1-7, comprising: (1) Preparation of three-dimensional graphene-supported sulfur mixture: sulfur powder and three-dimensional graphene are uniformly mixed and heated to the melting point of sulfur, so that the sulfur melts and penetrates into the pores of graphene to obtain a three-dimensional graphene-supported sulfur mixture. (2) Preparation of functionalized positive electrode: The above three-dimensional graphene-supported sulfur mixture is uniformly mixed with a binder, and a solvent is optionally added; the prepared mixed slurry is loaded onto the surface of the current collector and dried to obtain a functionalized positive electrode film; (3) Preparation of lithium composite anode space layer: MOFs material, lithium salt, binder and hydrophilic additive are uniformly mixed, and an optional solvent is added and stirred to obtain a mixed slurry. The mixed slurry is placed on the transfer film and dried to obtain lithium composite anode space layer. (4) Preparation of lithium composite anode: The space layer film is rolled onto the surface of the lithium / lithium alloy anode and the tabs are welded to obtain the lithium composite anode; (5) Assemble lithium-sulfur solid-state batteries: Assemble functionalized positive electrode, solid electrolyte, lithium composite negative electrode and encapsulation materials into lithium-sulfur solid-state batteries.

9. The method according to claim 8, characterized in that, The uniform mixing method described in step (1) is ball milling, wherein the ball milling speed is 100-600 rpm and the ball milling time is 3-6 h; The drying process described in steps (2) and (3) is at 80-100℃ and takes 8-12 hours. The adhesive mentioned in step (2) includes at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), sodium alginate (SA), polyethylene oxide (PEO), or polyimide (PI); The solvents mentioned in steps (2) and (3) include any one or a combination of at least two of N-methylpyrrolidone, tetrahydrofuran, dimethyl ethyl ether, dichloromethane, ethylene carbonate, dimethyl carbonate, diethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene glycol dimethyl ether, diethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, dimethyl sulfate, and polyetherketone; In step (2), the three-dimensional graphene loaded with sulfur: binder: solvent = (5-10): (2-3): (87-93).

10. The method according to claim 8, characterized in that, Step (3) The method of applying the paste to the transfer film includes any one or a combination of at least two of the following: coating, spraying, spin coating, rolling, and impregnation; In step (4), the pressure at which the space layer obtained in step (3) is rolled onto the lithium / lithium alloy negative electrode is 10-20 kN.